A STATISTICAL APPROACH TO GEOLOGICAL MAPPING - Ghosh J.K.; Bhanja J.; Purkayastha S.; Samanta T.; Sengupta S. (My University, 2002)
A geological map is the representation, on a two-dimensional plane, of the disposition of three-dimensional rock bodies exposed on the earth's surface. The problem of mapping is essentially that of dividing an area into "homogeneous" subregions on the basis of the exposed rock types. Automatic Bayesian methods of model selection using default Bayes factors have been employed to solve the problem of choosing a set of boundaries between "homogeneous" subregions, assuming no complication excepting low-angle tilting affected rock bodies. The method is tested on two data sets. A sampling scheme for optimum allocation of observation points is also presented.
Keywords: BAYES FACTOR; BAYESIAN MODEL SELECTION; FRACTIONAL BAYES FACTOR; INTRINSIC BAYES FACTOR; MINIMAL TRAINING SAMPLE; NON-INFORMATIVE PRIOR